The Role of Maternal Stress Epigenetics in the Risk of Stunting among Children Aged 0–24 Months: A Community-Based Longitudinal Study - Juli Purnama Hamudi; Via Zakiah; Harni Harni (Newinera Publisher, 2026)
Stunting is a major child health problem influenced by multiple factors, including maternal conditions during pregnancy. This study aimed to analyze the relationship between maternal stress, epigenetic mechanisms, and the risk of stunting in children aged 0–24 months. A community-based prospective longitudinal cohort design was employed, involving 30 pregnant women who were followed until their children reached 24 months of age. Maternal stress was assessed using the Perceived Stress Scale (PSS), while epigenetic analysis was conducted via DNA methylation of the IGF2 gene from umbilical cord blood samples. Stunting status was determined based on length-for-age (LAZ) according to WHO standards. The results indicated a tendency toward an increased risk of stunting among mothers with high stress levels (OR=9.00; p>0.05), along with increased IGF2 methylation. Although not statistically significant, the pattern of association was clinically consistent. It is concluded that maternal stress may increase the risk of stunting through epigenetic mechanisms. Integrating stress management into antenatal care is recommended as a strategy for stunting prevention.